Nutritional Status of Child Under Five Years Model based of Consumption, Behavior, Biology and Environment Factors - I. , Komang Agusjaya Mataram; Putu Agustini, Ni; Laraeni, Yuli; A., A. Raka Sudewi; I. , Gde Raka Widiana; A., A. Gde Muninjaya (International Journal of Psychosocial Rehabilitation, 2020)
Malnutrition problem is one of the major public health problems in Indonesia. In Pengotan village, as one of the traditional villages of Bali, malnutrition problems among child under five still exist. The local community has a unique traditional way of life. However, the majority of the households are poor which lack of education, low income, and own limited land. The objective of this cross-sectional survey was to investigate the nutrition status model of Pengotan village based on consumption, behavior, biology and environmental factors. Confirmatory Factor Analysis (CFA) showed that behavior and consumption can be continued to analyze Structural Equation Model (SEM). However, biology and environment factors were not appropriate to be used. The final model that fit to nutrition status was behavior (r=0,389) and consumption factors (r=-0,254).Factors affected nutrition status among others were food, infection, food intake and utilize, environment, lifestyles, medical care and heredity, biology, environment, and behavior. However, this study found that dominant factors related to nutrition status of children under five in Pengotan village were behavior and consumption factors.